Amperometric determination of electroosmotic flow in microchip electrophoresis with a self-generated marker. (20th August 2015) - Chen, Chi-Hao; Lin, Meng-Shan
Graphical abstract: Highlights: A novel amperometric method to estimate the EOF through the dissolved oxygen in the buffer. No complicated program or physical alteration of the electrolyte is used in this scheme. A self-generated EOF marker is produced on the decoupler electrode before each electrophoresis. Simultaneous evaluation of the EOF and the electrophoretic property of several analytes is achieved. Abstract: This work described a novel method to evaluate the electroosmotic flow (EOF) without using any complicated electric profile or physical modification of the running buffer. In a typical off- channel based microfludic device, it is found the carbon ink based decoupler electrode maintains its reduction capability after the electric field is turned off, this phenomenon makes it continually converts the dissolved oxygen into hydrogen peroxide. Since the electric field is isolated before the decoupler electrode, this in-situ generated sample plug is delivered to pass through the detector with an equal velocity to the EOF in the next run. Therefore, the velocity of EOF can be easily estimated based on the migration time and the distance between the decoupler and the working electrode. Subsequently, the application of simultaneous evaluation of the velocity of EOF and the electrophoretic property of several analytes, including catechol, 2-aminophenol, dopamine and hydrogen peroxide have been also demonstrated in this method, respectively.